Préparation du charbon à partir des déchets agricoles, application dans le traitement des eaux - كمال, عبية; سهيل, نصري; نور الدين, زين (University of El-Oued, 2021)
"The remains of toxic pharmaceutical substances in aquatic environment can causes many environmental risks, so it was necessary to research techniques to reduce their effects. The objective of this study is the valorization of a natural residue, namely sawdust, and converted it into biochar with a good porous structure and important specific surface area to eliminate the pollutant from water (ibuprofen). In the first chapter, we dealt with general information about pharmaceutical substances, their sources and their danger to the ecosystem, in particular ibuprofen. In addition, the generalities about the absorption phenomenon and its types, the factors that affect them and the ways to product activated carbon. In the second chapter, we discussed the materials and means used in the experiments, as well as the preparation of biochar by pyrolysis at 600 degrees, and all experiments including the study of the properties of carbon, experiments of the ibuprofen adsorption onto the prepared adsorbent and effect of the related factors. Through all the obtained results, we concluded the following: The adsorption capacity of SB600 vis-à-vis ibuprofen ions is very important and it depends on several factor, better ibuprofen removal efficiency is obtained at: t = 120 min, v = 180 tr/ min, pH= 7, Co = 30 ml/g, T= 25 °C . The kinetics data obeys the pseudo-second order model and the Langmuir model correctly describes the adsorption isotherm. " "تسبب بقايا المواد الصيدلانية السامة الكثير من الكوارث البيئية لذا وجب البحث عن تقنيات للحد من خطورتها. الهدف المنشود من هذه المذكرة هو تثمين بقايا المواد الطبيعية وبالتحديد نجارة الخشب وتحويلها الى كربون منشط ذو بنية مسامية ومساحة نوعية مهمة لإزالة الملوث ايبوبروفين. تناولنا في المحور الاول معلومات عامة حول المواد الصيدلانية مصادرها وخطورتها على النظام البيئي ونخص بالذكر ايبوبروفين كما تطرقنا الى عموميات حول ظاهرة الامتصاص انواعها والعوامل المؤثرة عليها وطرق تحظير الكربون المنشط. في المحور الثاني تطرقنا الى المواد والوسائل المستعملة في التجارب وكذا تحضير الكربون المنشط عن طريق الانحلال الحراري في درجة 600 درجة مئوية واداء كل التجارب بداية بدراسة خصائص الكربون ومدى تأثيرهم، الى التجارب الخاصة بامتزاز ايبوبرفين بواسطة الكربون المنشط والعوامل المؤثرة على فعالية الامتزاز نذكر منها زمن التخليط، التركيز الاولي للملوث، وحموضة المحلول. وخلال جميع النتائج المحصل عليها في التجارب استنتجنا ما يلي الفحم المنشط المحضر قدرة عالية على امتزاز ايببروفين وتتأثر بعدة عوامل منا الخاصة بالفحم في حد ذاته ومنها خاصة بظروف التجربة والمفاعلات. وقد تم الحصول على افضل فعالية في الظروف التالية: درجة حرارة =°C 25 وزمن تخليط = min 120 سرعة تخليط = tr/min 180 وتركيز اولي = ml/g30. نموذج pseudo-second order يصف بشكل صحيح حركية الامتزاز ونموذج Langmuir يصف متساوي الحرارة "
Conception et diagnostic du système d'AEP et d'Assainissement- مذكرة ماستر تخصص
Keywords: Adsorption, ibuprofen, biochar (SB600), kinetics, isotherm; الامتزاز، ايبوبروفين,( ibuprofène) الفحم النباتي ,( SB600) الحركية، الأيسوثرم.